Perhatian Orang Tua terhadap Masalah Belajar Anak di Kanagarian Pulakek Koto Baru - Norita, Riza Vefri; Putra, Dodi Pasila (MASALIQ, 2023)
Parents' attention to children's learning problems is lacking, parents ignore children's learning problems, parents leave early in the morning and come home in the evening to earn a living, generally as farmers. The purpose of this study was to determine the attention of parents in Kangarian Pulakek Koto Baru to the learning problems of elementary school level children, which are related to attention to children's discipline in learning, homework, completeness of learning facilities, textbooks, and guiding children in learning. The research method is a qualitative descriptive method. Key informants were parents of children and informants supporting the nagari nagari guardians and children of both high school and junior high school students in Kanagarian Pulakek Koto Baru. The research results show; 1) the attention of parents in Kanagarian Pulakek Koto Baru to the discipline problem of children learning less, 2) the attention of parents in Kanagarian Pulakek Koto Baru has not given enough attention to their children in doing schoolwork at home, 3) the attention of parents in Kanagarian Pulakek Koto There is also a lack of new learning facilities for children and 4) The attention of parents in Kanagarian Pulakek Koto Baru in guiding their children to study at home is very lacking. Based on the data above, it can be concluded that parents in Kangaria Pulakek Koto Baru still do not pay enough attention to the learning problems faced by their children.